2020
DOI: 10.1007/978-3-030-52869-0_15
|View full text |Cite
|
Sign up to set email alerts
|

Built Environment and Alzheimer. Quality Evaluation of Territorial Structures for Patients with Dementia

Abstract: Sustainable, inclusive and resilient cities and urban settlements are fundamental in enabling people to live long and healthy lives. Elderly population is growing all over the world and in Italy is among the largest. Within this scenario, epidemiological data show that Alzheimer disease, a dementia which manifest with ageing, is also forecast to rapidly increase, up to 150 million cases in 2050. Within urban settlements, the health and socio-sanitary structures for elderly patients represent a fundamental soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…The biophysical dimension revealed that there is a lack of systematic information about the state of housing accessibility in the ordinary housing stock, as well as a low level of knowledge and insufficient evidence on the health and wellbeing impacts on individuals and society. Here, the application of performance-based assessment methodologies for quality evaluation of built environments (see e.g., [38,39]) might have the potential to contribute to the much-needed evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…The biophysical dimension revealed that there is a lack of systematic information about the state of housing accessibility in the ordinary housing stock, as well as a low level of knowledge and insufficient evidence on the health and wellbeing impacts on individuals and society. Here, the application of performance-based assessment methodologies for quality evaluation of built environments (see e.g., [38,39]) might have the potential to contribute to the much-needed evidence base.…”
Section: Discussionmentioning
confidence: 99%
“…The checklist has been created according to design guidelines and strategies (Brambilla, Maino, et al, 2020) derived from a systematic literature review, case studies, and tools already in use. This allows us to understand which fundamental aspects are to be considered and implemented in a healthcare facility that can accommodate patients with dementia and Alzheimer's disease.…”
Section: Theories and Methodsmentioning
confidence: 99%
“…The pandemic emergency has highlighted the weakness of the health system, placing a heavy burden on hospital centers and especially on emergency departments; therefore, it is pivotal to achieve more extensive and homogeneous levels of service, reduce hospitalization demand, and use digitalization and telemedicine tools, where applicable, to monitor the health of citizens. This change will not be able to disregard the management of an efficient network of places intended for other forms of assistance and the concrete involvement of home care, increases in rehabilitation hospitalization facilities, health residences, and territorial outpatient clinics, and the careful management of services that precede rapid and targeted therapeutic interventions in hospitals [79,80].…”
Section: Re-thinking Community Servicesmentioning
confidence: 99%